2018
DOI: 10.1111/are.13852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of yeast and bacterial based probiotics for early rearing of Labeo rohita (Hamilton, 1822)

Abstract: Relatively poorly developed digestive and immune systems appear as key factors for low survivability and reduced growth rate of major carp during early development stages. Here, an attempt has been made to improve the digestive capability and immune response of Labeo rohita larvae by feeding diets supplemented with yeast and bacterial based probiotics Geotrichum candidumQAUGC‐01 and Bacillus cereus,locally isolated from yogurt and gastrointestinal tract of an adult healthy L. rohita respectively, and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
19
2
Order By: Relevance
“…84 Both alginates and probiotics have been reported for their role in improving immunological response during the early rearing cycle of fishes. 88 This has been substantiated by an equivalent study on L. rohita, 89 and further elaborated with the augmentation of haematoimmunological indices and modulation of immune-responsive gene expression, in L. rohita fingerlings. 84 In addition to yeast cells and fungal probiotic species, Bacillus species have been reviewed as the most suitable probiotic candidates for potentiating the immune health of aquatic animals.…”
Section: Mono-species Probioticsmentioning
confidence: 85%
“…84 Both alginates and probiotics have been reported for their role in improving immunological response during the early rearing cycle of fishes. 88 This has been substantiated by an equivalent study on L. rohita, 89 and further elaborated with the augmentation of haematoimmunological indices and modulation of immune-responsive gene expression, in L. rohita fingerlings. 84 In addition to yeast cells and fungal probiotic species, Bacillus species have been reviewed as the most suitable probiotic candidates for potentiating the immune health of aquatic animals.…”
Section: Mono-species Probioticsmentioning
confidence: 85%
“…The administration of yeast S. cerevisiae alone elicited higher growth of common carp in comparison to a mixture of S. cerevisiae with L. acidophilus (Dhanaraj et al 2010). Similarly, the yeast Geotrichum candidum presented higher intestinal enzyme production and survival after an experimental infection with A. hydrophila in rohu, in comparison to its mixture with B. cereus (Amir et al 2018). Park et al (2016) showed in rainbow trout that B. subtilis administered as a monostrain yielded better growth performance than when combined with B. licheniformis.…”
Section: Discussionmentioning
confidence: 97%
“…Only two of the 81 studies measured probiotic viability at various times and temperatures. Using plate counts, Amir et al (2018) examined the viability of fungal and bacterial strains before and after feed preparation and during feed storage, but the results were not published. Aly et al (2008a) assessed weekly the viability of three Nile tilapia dietary probiotic bacteria during storage over 5 weeks at 4 and 25°C, showing that viability varied with storage temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A control diet without Co supplementation was also prepared. Feed pellets were prepared following standard methods, dried and saved in Ziploc bags as described previously (Amir et al 2018). Fresh feed was prepared after every 15 days.…”
Section: Diet Preparationmentioning
confidence: 99%